Melioidosis an Emerging Disease in the Indian Ocean Region: Case Series Study in Mayotte (Global Journal of Medical Research, 2023)
Background Burkholderia pseudomallei is the agent of melioidosis It is a bacterium from the hydrotelluric environment highly pathogenic for humans The geographical distribution of this disease is spreading and now affects the southwest of the Indian Ocean and in Mayotte Case presentation We report four new cases of melioidosis with a case that was complicated by a failure of several organs case 2 which were observed on Mayotte Island The last two affected cases came from Madagascar Burkholderia pseudomallei was isolated from blood cultures confirming the diagnosis Prolonged treatment with ceftazidime or Ertapenem intravenously followed by cotrimoxazole alone or combined with oral doxycycline led to complete recovery
Keywords: burkholderia pseudomallei; melioidosis; Mayotte